Organophotoredox-Catalyzed Oxidative C(sp2)–H Alkylation of N-Heteroarenes with Dihydroquinazolinones by C–C Cleavage - Mondal, Pinku Prasad; Pal, Amit; Das, Subham; Vijayan, Sariga Mangalamundackal; Nair, Anagha Veluthanath; Ojha, Shubham; Sahoo, Basudev (Synlett, 2023)
We report a visible-light-mediated, organophotoredox-catalyzed, C(sp2)–H alkylation of N-heteroarenes with dihydroquinazolines, prepared from aliphatic ketones, under oxidative conditions. This protocol represents a metal-free approach to the effective construction of C–C bonds through a Minisci-type reaction, formally activating the native C–H bond of the N-heteroarene and an α-C–C bond of a readily available ketone. The mild nature of this method accommodates a wide variety of N-heteroarenes and ketones, tolerating a wide range of functional groups.
Keywords: photoredox catalysis; heteroarenes; ketone; C–C bond cleavage; alkylation